Efficacy of an Emergency Cervical Cerclage Using Absorbable Monofilament Sutures. (26th November 2018) - Sato, Yuka; Hidaka, Nobuhiro; Nakano, Takahiro; Kido, Saki; Hachisuga, Masahiro; Fujita, Yasuyuki; Kato, Kiyoko
Abstract : Introduction . Although nonabsorbable woven tape has been widely used for cervical cerclage, technical difficulties that can occur with an effaced cervix because of the thickness of the tape, and the risks of local infection are two major concerns. This study investigated perinatal outcomes of pregnancies involving an emergency cervical cerclage using absorbable monofilament polydioxanone sutures, which is a narrow thread and protects against bacterial infection. Materials and Methods . We performed a chart review of patients who underwent emergency McDonald cerclage with polydioxanone sutures at our institution between 2007 and 2015. Gestational age at delivery, duration between cerclage and delivery, and neonatal prognosis were evaluated as primary outcomes. Results . Among the 23 patients (18 singleton and five twin pregnancies) evaluated, ultrasound-indicated (progressive cervical length shortening) were eight (35%) and physical examination-indicated (fetal membranes that prolapsed into the vagina or dilated cervix) were 15 patients (65%). The median gestational age at cerclage was 22 +3 weeks (range, 17 +5 to 25 +3 weeks). Postoperative spontaneous abortion occurred in only one patient. The median gestational age at delivery was 32 +5 weeks (range, 20 +5 to 40 +6 weeks). Extremely preterm delivery before 28 weeks of gestation occurred in four (17%) cases. Full-term delivery was achieved in 10 (42%) cases. The duration between cerclage and delivery ranged from 5 to 136 days (median, 77 days). Except for one case of spontaneous abortion, all newborns survived till hospital discharge. Conclusions . Although our series included some patients at high risk for spontaneous abortion and preterm delivery, satisfactory prolongation and favorable neonatal outcomes were achieved for most patients by using absorbable monofilament sutures, thus suggesting the efficacy of this type of suture for emergency cervical cerclage.